Overview of cement and concrete production in Latin America and the Caribbean with a focus on the goals of reaching carbon neutrality - Yury Villagrán-Zaccardi; Ricardo Pareja; Lina Rojas; Edgardo Fabián Irassar; Andrés Torres-Acosta; Jorge Tobón; Vanderley M. John (RILEM Technical Letters, 2022)
Carbon neutrality to limit global warming is an increasing challenge for all industries, particularly for the cement industry, due to the chemical emission of the process. For decades, reducing the clinker factor has been one of the main strategies to reduce the carbon footprint. Additional cuttings in the clinker content of cements seem possible with the upsurge of novel supplementary cementitious materials. This potential contribution represents only a fraction of the required carbon reductions for achieving the goal of carbon neutrality in the coming decades. This paper describes the current situation of the cement industry in Latin America and the Caribbean and the global opportunities and strategies to reduce the carbon footprint of cement and concrete and their adaptation to the regional conditions. Besides describing emerging supplementary cementitious materials, the potential contributions of industrialization and quality control are discussed. Moreover, limitations related to geography and standardization are analyzed. Regional considerations are made given the specific prospects of human development.